The risk of eating disorders in adolescent athletes: How we might address this phenomenon? - Rojas-Padilla, I. C.; Portela-Pino, I.; Martínez-Patiño, M. J. (Sports, 2024)
Eating disorders are psychiatric and behavioral health pathologies of high complexity and different etiology, which can affect age groups, sexes, and ethnicities indistinctly. This study aimed to evaluate the risk of eating disorders and the possible relation with the sports profile of Colombian adolescent athletes. This was an exploratory cross-sectional quantitative study that used an online form designed with a sociodemographic questionnaire and the EAT-26 scale to determine the eating disorder risk of the object population. A total of 354 adolescent athletes participated. There were 182 men and 172 women and the mean age was 15.59 (range: 10-19 years, SD = 1.938). The participants presented a significantly low risk of eating disorders (21.2%) with no differences in prevalence between both sexes. The risk of eating disorder was related to the result of the last competition (p = 0.01), the type of sport (p = 0.032), the years of sports practice (p = 0.004), and the number of training hours a day (p = 0.011). It is relevant to recognize that adolescents and athletes are vulnerable populations regarding eating disorders. In conclusion, adolescent athletes should be the object of special attention to prevent eating disorders and their consequences on health and sports performance.